2021
DOI: 10.1080/21505594.2021.1972538
|View full text |Cite
|
Sign up to set email alerts
|

Colibactin in avian pathogenic Escherichia coli contributes to the development of meningitis in a mouse model

Abstract: Colibactin is synthesized by a 54-kb genomic island, leads to toxicity in eukaryotic cells, and plays a vital role in many diseases, including neonatal sepsis and meningitis. Avian pathogenic Escherichia coli (APEC) is speculated to be an armory of extraintestinal pathogenic Escherichia coli and can be a potential zoonotic bacterium that threatens human and animal health. In this study, the APEC XM meningitis mouse model was successfully established to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 83 publications
0
12
0
Order By: Relevance
“…coli [ 6 ]. Previous studies showed that the deletion of clbG or clbH abolished the production of colibactin and then affected the development of meningitis in mice induced by APEC [ 30 , 31 ]. This study demonstrated that the deficiency of clbA significantly attenuated APEC virulence in systemic infections and the process of meningitis development including bacteremia, penetration of the BBB and induction of pro-inflammatory factor expression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…coli [ 6 ]. Previous studies showed that the deletion of clbG or clbH abolished the production of colibactin and then affected the development of meningitis in mice induced by APEC [ 30 , 31 ]. This study demonstrated that the deficiency of clbA significantly attenuated APEC virulence in systemic infections and the process of meningitis development including bacteremia, penetration of the BBB and induction of pro-inflammatory factor expression.…”
Section: Discussionmentioning
confidence: 99%
“…Due to a pleiotropic phenotype of clbA mutant related to colibactin and siderophores, this reduction of BBB disruption could be caused by a direct or indirect combined effects of colibactin and siderophores. The previous study showed that colibactin contributed to serum resistance ability of APEC [ 30 ]. Deletion of colibactin-encoded genes such as clbH , clbG decreased the bacterial load in the blood of APEC infected mice [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epithelial cells exhibit DNA damage, cell cycle arrest, senescence and death upon exposure to pks + bacteria (11). Colibactin induces apoptotic cell death in lymphocytes and promotes virulence of pks+ E. coli during sepsis and meningitis (1214). Colibactin is also produced in the gut by commensal pks + E. coli and inflicts DNA damage in intestinal epithelial cells (1517).…”
Section: Introductionmentioning
confidence: 99%
“…Epithelial cells exhibit DNA damage, cell cycle arrest, senescence and death upon exposure to pks+ bacteria (11). Colibactin induces apoptotic cell death in lymphocytes and promotes virulence of pks+ E. coli during sepsis and meningitis (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%